Rekonstruksi Adab Sebagai Fondasi Peradaban Dalam Pendidikan Islam - Imam Mustakim (Jurnal Adab dan Peradaban Islam, 2026)
This study examines the reconstruction of adab (Islamic ethics and conduct) as a civilizational foundation in Islamic education. The research aims to analyze how adab can be repositioned as a foundational framework in the intellectual, moral, and institutional development of contemporary Islamic educational systems. Using a qualitative approach with library research design and content analysis, this study draws upon classical Islamic manuscripts, historiographical texts, and contemporary Indonesian scholarship. The findings reveal that adab serves not merely as an individual code of conduct, but as a comprehensive paradigm integrating scholarly ethics, pedagogical principles, aesthetic sensibilities, and social norms. The revitalization of adab within educational institutions provides a holistic model that unifies diverse learners under a shared intellectual and moral identity. This study concludes that adab constitutes a civilizational heritage of profound relevance for the reformation of contemporary Islamic education and the renewal of Muslim intellectual and moral culture.